THE ROLE OF THE FAMILY AND SOCIAL ENVIRONMENT IN THE CHILD'S MENTAL DEVELOPMENT (Universal International Scientific Journal, 2026)
In the course of personality development, the factors affecting the formation ofconsciousness, character, emotional state and social adaptation in the stages of childhood,adolescence, youth and adulthood are highlighted. The article justifies the importance ofconsidering age-related psychological characteristics in the process of education, in the design ofeducational work and social environment. The results of the research are explained to strengthenthe individual approach in working with the young generation, improve pedagogical strategies andeffectively organize psychological support mechanisms.
Keywords: age periods; psychological development; personality formation